A Cooperative Spectrum Sensing Strategy for Dynamic Cognitive Radio Sensor Networks - Kaschel-Carcamo, H; Toledo-De la Garza, K (Institute of Electrical and Electronics Engineers Inc., 2018)
Spectrum scarcity in Wireless Sensor Networks (WSN) has been commonly addressed by Cognitive Radio (CR) technology. This has contributed to the emerging paradigm called Cognitive Radio Sensor Networks (CRSN). This work is motivated by the imminent implementation of mobile sensor networks for Internet of Things (IoT). Cooperative Spectrum Sensing (CSS) is most widely used strategy to figure out the hidden terminal problem. In this regard, we determine the number of awake sensors over a dynamic environment to spectrum sensing. A mobility model for sensors is described by means of Markov chains. A first approximation of this kind of scenarios has described based on convex optimization. The proposed solution minimizes the energy consumption subject to constraints on detection performance. The analysis and performance of the proposed system are discussed and illustrated with the aid of simulations. © 2018 IEEE.